Solve travelling sales man problem by using fuzzy multi-objective linear programming - بطيخ عباس حسين (Journal of Economics and Administrative Sciences, 2014)
The main focus of this research is to examine the Travelling Salesman Problem (TSP) and the methods used to solve this problem where this problem is considered as one of the combinatorial optimization problems which met wide publicity and attention from the researches for to it’s simple formulation and important applications and engagement to the rest of combinatorial problems , which is based on finding the optimal path through known number of cities where the salesman visits each city only once before returning to the city of departure n this research , the benefits of( FMOLP) algorithm is employed as one of the best methods to solve the (TSP) problem and the application of the algorithm in conjunction with one . Mathematical model has been established based on unit objective, regarding each objective of the problem, and then establishing a mathematical model, with many objectives to apply the foggy method of many objectives.